2011
DOI: 10.1002/adfm.201100884
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Of Dielectric Permittivity And Electromechanical Response In Silicone Elastomers: Molecular Grafting Of Organic Dipoles To The Macromolecular Network

Abstract: A novel method is established for permittivity enhancement of a silicone matrix for dielectric elastomer actuators (DEAs) by molecular level modifi cations of the elastomer matrix. A push-pull dipole is synthesized to be compatible with the silicone crosslinking chemistry, allowing for direct grafting to the crosslinker molecules in a one-step fi lm formation process. This method prevents agglomeration and yields elastomer fi lms that are homogeneous down to the molecular level. The dipole-to-silicone network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
190
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 34 publications
4
190
1
2
Order By: Relevance
“…TiO 2 -silicone composites have by far been the most commonly investigated elastomer system due to the availability of nanosized TiO 2 particles with various surface functionalizations. More complex approaches exist such as the covalent grafting of dipoles [11][12][13] and the creation of heterogeneous elastomers with hard and soft domains from controlled network formation [14][15][16][17]. Incorporating rigid fillers, such as titanium dioxide, into the cross-linked PDMS matrix increases the dielectric permittivity of the resulting composite elastomer.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 -silicone composites have by far been the most commonly investigated elastomer system due to the availability of nanosized TiO 2 particles with various surface functionalizations. More complex approaches exist such as the covalent grafting of dipoles [11][12][13] and the creation of heterogeneous elastomers with hard and soft domains from controlled network formation [14][15][16][17]. Incorporating rigid fillers, such as titanium dioxide, into the cross-linked PDMS matrix increases the dielectric permittivity of the resulting composite elastomer.…”
Section: Introductionmentioning
confidence: 99%
“…There are generally three routes for enhancing the dielectric constant of an elastomer, which include addition of high permittivity inorganic particles [24,25], addition of conductive fillers [26] and chemical design [27]. Chemical design involves polymer chain modification.…”
Section: Elastomers 234mentioning
confidence: 99%
“…Furthermore the grafting should provide more stable systems upon continuous activation of the materials. Risse et al 15 showed that vinyl-functional dipoles could be added to commercial silicones together with a compensating amount of hydride-functional crosslinker and thereby the dielectric permittivity could be increased significantly. Madsen et al 16 used a similar approach but with one dipole being specifically grafted on one crosslinker by use of click chemistry.…”
Section: Introductionmentioning
confidence: 99%